Social Unrest and Distrust - Pamerdyatmaja, Pamerdyatmaja (Humaniora, 2024)
Shadow Play provides an insight into urban studies in Indonesia by showing Yogyakarta as a space of interaction with research on relocation among development discourses. Relocation was often under the unilateral regulatory power of the state (government) in the new order era. Gibbings offers a new perspective in which the relocation of traders is not solely focused on the displacement of a group of people but shows the tug-of-war in drafting agreements after the authoritarian regime's collapse through the 1998 reform agenda. In this book, Gibbings includes two introductory arguments to evoke the reader. First, the study of politics and information control is a subject relation that can change at any time, along with the involvement of stakeholders daily. Second, by focusing on the politics of information, Gibbings exposes the relationship between the state and its citizens, particularly in post-authoritarian situations.